1992
DOI: 10.1111/j.1399-6576.1992.tb03458.x
|View full text |Cite
|
Sign up to set email alerts
|

Spinal sufentanil in rats: part II: effect of adding bupivacaine to epidural sufentanil

Abstract: Male Wistar rats were injected epidurally with various doses of sufentanil, bupivacaine or sufentanil combined with bupivacaine either 40 or 80 micrograms. Addition of 80 micrograms bupivacaine to sufentanil produced a 2.2- to 3-fold decrease of the lowest ED50 for a tail withdrawal reaction latency greater than 6 and greater than or equal to 10 s. The potentiation was already present at low doses. Whereas both 0.16 microgram sufentanil and 80 micrograms bupivacaine were inactive, the combination of the two dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1993
1993
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Indeed, local anaesthetics and morphine have been described to synergistically interact with each other in preclinical studies without the appearance of motor blockade (Maves and Gebhart, 1992; Penning and Yaksh, 1992). However, previous studies have also demonstrated a synergy between lipophilic opioids and local anaesthetics (Vercauteren et al, 1992; Vercauteren and Meert, 1997). Therefore, if the local anaesthetic effect of ketamine would be involved in the potentiation of morphine, we would have observed some potentiation of fentanyl‐induced antinociception.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, local anaesthetics and morphine have been described to synergistically interact with each other in preclinical studies without the appearance of motor blockade (Maves and Gebhart, 1992; Penning and Yaksh, 1992). However, previous studies have also demonstrated a synergy between lipophilic opioids and local anaesthetics (Vercauteren et al, 1992; Vercauteren and Meert, 1997). Therefore, if the local anaesthetic effect of ketamine would be involved in the potentiation of morphine, we would have observed some potentiation of fentanyl‐induced antinociception.…”
Section: Discussionmentioning
confidence: 96%
“…Os grupos experimentais (n=7 Ratus novergicus por grupo) estabelecidos para a realização da atividade analgésica são apresentados na Figura 16. A concentração de SUF foi de 38,8µM ou 15μg.mL -1 (Vercauteren et al, 1992) administrado nas formas livre, associado à BVC e ao complexo BVC:H-β-CD.…”
Section: Gruposunclassified